Test Of The FAMA And French Three Factor Model And Its Variant In Bursa Malaysia - Monfared, Mahdi Mohammadzadeh (2011)
This paper empirically studies the FAMA and French three-factor model of stock returns along with its variants, for the Malaysian manufacturing industry, which consists of 325 companies listed on the Main board of the Bursa Malaysia from January 2006 to December 2009.